(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The modern computing world revolves around the word “DATA”, but just what is so intriguing about it? In today’s world, data is the power and business start realizing it because data can predict customer trends potentially, get increased sales, and help the organization to achieve newer heights. The technology has become so advanced and our topmost priority is to secure data.Here in this project, the high frequency coefficients produced by the discrete wavelet transform contain hidden messages. To enhance the quality of the images, low frequency sub-band coefficients are kept intact. Before embedding, some elementary mathematical operations are performed on the secret messages. These operations prevent messages from being stolen or destroyed by unauthorized internet users, and they do so while also providing adequate security.